IMPLEMENTATION OF SCHOOL PRINCIPAL MANAGERIAL SUPERVISION IN IMPROVING TEACHER DISCIPLINE AT SMP NEGERI 1 SIMPANG EMPAT - Syakwanah, Syakwanah; Zein, Achyar; Budianti, Yusnaili (UIN Sumatera Utara Medan, 2023)
This article aims to reveal how Managerial Supervision improves Teacher Discipline at SMP Negeri 1 Simpang Empat. This research uses qualitative research, with research examining directly in the field. The data collection techniques used by researchers were interviews and observations with teachers and documentation carried out by researchers in the field in order to strengthen the validity of the research data. The results of these findings include five findings: 1) Managerial supervision at SMP Negeri 1 Simpang Empat has been carried out well and in accordance with the goals and roles of the managers themselves, 2) Teacher discipline at the school is in the disciplined category. 3) the driving and inhibiting factors for teacher discipline in this school. Almost all the information that researchers have obtained is that there are two factors, namely from the individual himself (internal) and from leaders, co-workers or other demands (external). 4) Managerial supervision in improving teacher discipline at SMP Negeri 1 Simpang Empat has had very good implications, with the supervision carried out by the principal of teachers. 5) In implementing managerial supervision, school principals have their own steps in controlling the discipline of teaching staff with persuasive actions.